Return On Asset dan Resiko Sistematis Terhadap Harga Saham Sektor Pertambangan Di Jakarta Islamic Index (JII) Pada Tahun 2018-2021 (Institut Agama Islam Negeri Kudus, 2023)
This study aims to determine the relationship and influence of return on assets (ROA) and systematic risk on mining sector stock prices in JII (Jakarta Islamic Index). Stocks from the mining sector are also part of the blue-chip stocks which are known as stocks that have good fundamentals and relatively stable prices. However, the IHSG experienced price fluctuations during the Covid 19 pandemic. In addition, the ratification of the Minerba Law also prompted changes in share prices in the mining sector. The research method used is a quantitative method with a descriptive approach model. The research sample consisted of 11 mining companies with an observation period of 4 years. In conducting the analysis on the data is done by using a multiple linear regression model. The results of this study conclude that the variable return on assets (ROA) has a significant effect on mining stock prices in JII, with a t-count value of 3,032 which is greater than t-table with a value of 2,01954 with a significance value of 0,004 which is less than 0,05. Systematic risk variables have no significant effect on stock prices in JII, with a t-value of -1,964 which is less than t-table which is 2,01954 with a significance value of 0,054 greater than 0,05. But simultaneously or simultaneously, the two variables have an influence on mining stock prices in JII, with a calculated f value of 6,077 greater than the f table which is 3,23 with a significance value of 0,005 which is smaller than 0,05.